AaPP2C1 negatively regulates the expression of genes involved in artemisinin biosynthesis through dephosphorylating AaAPK1. Issue 7 (9th March 2019) - Zhang, Taixin; Gou, Yuqin; Bai, Feng; Bai, Ge; Chen, Min; Zhang, Fangyuan; Liao, Zhihua
Abstract : Artemisinin is biosynthesized in Artemisia annua and widely used for the treatment of malaria. Abscisic acid (ABA)‐responsive kinase 1 (AaAPK1), a member of the SnRK2 family, is involved in the regulation of artemisinin biosynthesis through the phosphorylation of AabZIP1, which directly transactivates genes involved in artemisinin biosynthesis. Through diverse assays – including yeast two‐hybrid and bimolecular fluorescence complementation assays – we report that the ABA‐responsive protein phosphatase AaPP2C1 physically interacts with AaAPK1. In addition, phos‐tag mobility shift assays indicate that AaPP2C1 dephosphorylates AaAPK1. Moreover, dual‐luciferase assays demonstrate that the presence of AaPP2C1 reduces the transactivation of artemisinin biosynthesis genes by AabZIP1. These results further refine the post‐translational regulatory network of artemisinin biosynthesis, showing that AaPP2C1 is negatively involved through dephosphorylation of AaAPK1. Abstract :